Market take-off in systemic industries: The early industry life cycle stage in the mobile payment industry - Raina König; Michael Stephan (Philipps-University Marburg, Department of Technology and Innovation Management, 2007)
The present discussion paper investigates the market dynamics in the early phase of an industrys life cycle. The industry life cycle model is so widely accepted and its basic premises so taken for granted that it has become conventional wisdom in business. However, a number of facets of the concept are still poorly understood mainly because of the lack of empirical evidence. E. g., while it is widely recognized that firms in the initial stage of the life cycle exist under conditions of significant uncertainty and ambiguity, little is known about the factors and processes that feed the establishment of a dominant design and that lead to sales take off and growth of the market. The present discussion paper develops a more detailed framework for the infant stage of an industry and subdivides the early life cycle stage for a new industry into three distinct, sequential time periods. Our more detailed perspective on the early stage benefits the analysis of which factors influence the emergence of a dominant design and attract a critical mass of customers. In our analysis we place an additional focus on systemic industries. By definition, industries are systemic in nature when the products are complex and composed of many interdependent elements, subsystems, modules, parts and services. In industries with complex products firms must rely on external suppliers and partners. We back our theoretical considerations with an empirical investigation into the mobile payment industry. The mobile payment industry is characterised by a highly systemic architecture and is still in the initial stage of the industry life cycle.
Keywords: 650